Budget Accountability in the Jayapura Regency DPRD Secretariat Qualitative Study - Wa Ode Sitti Nurhayati (Golden Ratio of Finance Management, 2026)
Budget accountability is an important aspect of regional financial management based on the principles of good governance, particularly transparency, accountability, effectiveness, and efficiency. This study aims to examine budget accountability in the Secretariat of the Jayapura Regency Regional Representative Council (DPRD) and identify factors that influence the effectiveness of its implementation. This study uses a descriptive qualitative approach, with data collected through in-depth interviews with five informants directly involved in budget management, as well as observation and documentation. The results show that procedural budget accountability is in accordance with the provisions of laws and regulations, but does not fully meet the principles of transparency, effectiveness, and performance accountability. The main problems found include low budget realisation due to delays in implementing activities, delays in submitting Accountability Reports (SPJ), inaccurate budget allocations, and a weak internal control system. In addition, disclosure of financial information to the public remains limited, and public participation in budget oversight remains suboptimal. Therefore, increasing human resource capacity, utilising information technology in financial reporting, and strengthening internal and external oversight are strategic steps to improve budget accountability in the Jayapura Regency DPRD Secretariat.